Adoecimento docente: um estudo da literatura a partir das teses e dissertações no período de 2007 A 2017 - SILVA, Evanilde Silva da (2020)
This study verifies what the Theses and Dissertations talk about the sickness of teachers, especially about the prevalence of diseases in Basic Education teachers in Brazil, from 2007 to 2017, and seeks to identify in those studies the factors that contribute to the occurrence of pathologies among these professionals, as well as their causes. For this, a bibliographic research of an exploratory nature was used as a methodological procedure, having as a data source the Theses and Dissertations on teaching sickness, defended in the Graduate Programs of the Federal Universities, cataloged at the Coordination Base for the Improvement of Personnel of Higher Level, in the mentioned period. At the end of the literature review, the results showed that the diseases that have most affected the health of the Brazilian Basic Education teachers are mental illness, voice disorder and Work-Related Musculoskeletal Diseases – DORT. conditions of teaching work, precariousness and intensification of work, subjecting teachers to the feeling of professional devaluation.